PEMANFAATAN SARANA DAN PRASARANA DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SDN PENGASINAN - Muhammad Hendri; Muhammad Yamin; Alfatih Rahman; Adelia Adelia; Ahmad Reva Farihan; Hendrayadi Hendrayadi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to describe the utilization of facilities and infrastructure and their impact on the quality of learning at SDN Pengasinan 01. The study used a qualitative approach with a descriptive approach. Data were collected through observation, interviews with the principal, teachers, students, and education staff, and documentation studies of inventory data and learning documents. The results indicate that facilities and infrastructure at SDN Pengasinan 01 are generally available, including classrooms, a library, sanitation facilities, teaching aids, and learning technology devices. However, their utilization in the learning process is not optimal and varies between classes and teachers, with basic facilities being used routinely while the library, teaching aids, and technology are used more incidentally. Appropriate utilization of facilities and infrastructure has been shown to have a positive impact on the quality of learning, including increasing student motivation, participation, and understanding of the material, as well as encouraging teachers to implement more varied and interactive learning methods, as confirmed by various previous research findings on the influence of learning facilities on learning quality. This study also identified barriers in the form of limited physical facilities and facilities, teacher competence and time in using media, and budget and external support limitations. This aligns with other studies on the impact of limited infrastructure on declining learning quality.